Kinerja Bidang Penataan, Pengawasan, dan Penegakan Hukum Lingkungan Dinas Lingkungan Hidup dalam aspek produktivitas permasalahan TPS Ilegal di Kecamatan Danau Sipin - Muhammad Alfarisy; Riri Maria Fatriani; Uswatun Asiah; Michael Lega (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2026)
The problem of illegal temporary shelters (TPS) is one of the serious environmental issues in Jambi City. Danau Sipin District is the district with the highest number of illegal TPS in Jambi City, namely 13 points. This study aims to determine the performance of the Environmental Management, Supervision and Enforcement Division (P3HL) the Jambi City Environmental Service the productivity aspect of the problem of illegal TPS in Danau Sipin District using the theory of public organization performance by Agus Dwiyanto (2006) with primary focus on productivity indicators. This can be seen from the utilization of various inputs such as human resources consisting of 3 field officers, operational facilities in the form of 1 patrol car, Standard Operating Procedures (SOP) for supervision, as well as clear and easy public reporting mechanisms to produce various outputs in the form of field supervision activities, enforcement of regulations, education and socialization to the public, and follow-up public reports. Although these various activities have been carried out, the limited number of field officers and operational facilities has resulted in the intensity of supervision in the field not being able to be carried out optimally. The conclusion of this study shows that the performance the Environmental Arrangement, Supervision and Law Enforcement Division of the Jambi City Environmental Service in terms of productivity has been running well, but still requires improvement, especially in the addition of human resources and operational facilities so that supervision and enforcement of regulations against illegal TPS can be carried out more optimally.